Youth Entrepreneurship Intentions: Insights from Surabaya’s Higher Education Institutions - Valentino Limbang Jaya; Helena Sidharta (Dinasti Publisher, 2025)
This study aims to examine the relationship between entrepreneurship education, entrepreneurial role model, entrepreneurial orientation, and entrepreneurial intention using path analysis. The respondents of this study were 158 students from a university in Surabaya who had completed the entire entrepreneurship curriculum. The researcher used SMART PLS 4 in the data processing. The results showed that entrepreneurship education affects entrepreneurial orientation. This study also showed that entrepreneurial role model affects entrepreneurial orientation. Furthermore, these results indicated that entrepreneurship education also affects entrepreneurial intention. Additionally, entrepreneurial role model influences entrepreneurial intention. Likewise, entrepreneurial orientation affects entrepreneurial intention. This study shows that entrepreneurial orientation acts as a mediating variable in the relationship between entrepreneurial role models and entrepreneurial intention, as well as mediating the relationship between entrepreneurship education and entrepreneurial intention. This indicates that entrepreneurial orientation as a mediating variable can be further explored, as previous studies did not show similar result.